2020
DOI: 10.1088/2053-1591/ab7c85
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous superconductivity in thin crystals of FeSe1−xTex (x = 1.0, 0.95, and 0.9)

Abstract: We investigated the temperature dependence of resistivity in thin crystals of FeSe 1−x Te x (x=1.0, 0.95, and 0.9), though bulk crystals with 1.0 × 0.9 are known to be non-superconducting. With decreasing thickness of the crystals, the resistivity of x=0.95 and 0.9 decreases and reaches zero at a low temperature, which indicates a clear superconducting transition. The anomaly of resistivity related to the structural and magnetic transitions completely disappears in 55-to 155-nm-thick crystals of x=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Here, salient resistance increase was observed at approximately 90 K. Li et al 24) reported that the increase in resistance is ascribed to the first-order magnetic and structural phase transition originating from FeTe. Furthermore, Eguchi et al 22) observed a similar resistance increase in FeTeSe, although they used non-magnetic electrodes. Therefore, the anomalous resistance increase is not attributed to the adjacent PMA electrodes.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Here, salient resistance increase was observed at approximately 90 K. Li et al 24) reported that the increase in resistance is ascribed to the first-order magnetic and structural phase transition originating from FeTe. Furthermore, Eguchi et al 22) observed a similar resistance increase in FeTeSe, although they used non-magnetic electrodes. Therefore, the anomalous resistance increase is not attributed to the adjacent PMA electrodes.…”
mentioning
confidence: 86%
“…The perpendicular magnetic field dependence of the Hall voltage (V Hall ) was measured by An FTS bulk single crystal was synthesized using the chemical vapor transport method, and an FTS thin film was mechanically exfoliated and transferred onto a SiO 2 (100 nm)/Si substrate using the scotch tape method. 21,22) Ar + milling was implemented to remove a possible oxidized layer on the FTS surface. The optical microscopy image of FTS after Ar + milling is shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] It is essential to synthesize high-quality FeSe1−𝑥Te𝑥 single crystals with bulk superconductivity for investigating the intrinsic physical properties. [9][10][11][12][13][14][15][16] The as-grown Fe 1+𝛿 Se1−𝑥Te𝑥 single crystals with the self-flux method inherently contains excess Fe atoms (𝛿 in quantity) for Te substitution 𝑥 > 0.5, which occupy the interstitial sites of the Fe(Se,Te) layers. [17] These interstitial irons are found to strongly suppress superconductivity and cause the physical properties to vary from sample to sample, [7,10,14,[18][19][20] interfering with a consistent understanding of the intrinsic physics.…”
mentioning
confidence: 99%